Localisation of calcium ions and calcium-ATPase activity within myelinated nerve fibres of the adult guinea-pig optic nerve. - Maxwell, W L (1991)
There is no published description of the distribution of free Ca2+, nor of the distribution of Ca(2+)-ATPase activity associated with the maintenance of low axoplasmic Ca2+ concentrations, in normal central myelinated nerve fibres. We have used the oxalate-pyroantimonate technique to localise free Ca2+, together with the lead-citrate technique to localise Ca(2+)-ATPase activity within myelinated fibres from the adult guinea-pig optic nerve. Pyroantimonate precipitate occurred within the axoplasm at nodes of Ranvier and the internode, at areas of myelin disruption, within Schmidt-Lanterman incisures (SLI) and glial paranodal loops. But precipitate was absent from the axoplasm beneath SLI and at the paranode. Ca(2+)-ATPase activity was localised in axonal smooth endoplasmic reticulum (SER), the outer membrane of mitochondria, the nodal axolemma, the glial membranes of the paranodal loops, the SLI and the external aspect of the myelin sheath. We have demonstrated large domains within the axons of CNS fibres where calcium is present or absent. Moreover, we have shown that, where calcium is absent, there is localisation of Ca(2+)-ATPase activity, which would serve to remove calcium from the adjacent axoplasm. Our results are compared with information obtained from PNS fibres and some differences of distribution discussed.